Seasonal Cycle of Leydig Cells in Birds - Muhammad Nazrul Islam; Masato Aoyama; Shoei Sugita (Achievements and Challenges of Medicine and Medical Science Vol. 4, 2024)
In seasonally breeding birds, an increase in testicular recrudescence mainly involves gamete production, Sertoli cell development and an increased number of Leydig cell production. After successful breeding, a rapid postnuptial testicular regression occurs. An investigation was done to elucidate seasonal histomorphological changes of Leydig cells in Japanese Jungle crows (Corvus macrorhynchos). Histologic data of Leydig cells regarding their locations in the interstitium, appearance and disappearance of lipoidal materials in their cytoplasm, and fibroblasts like precursor cells were studied. The photomicrographs were processed with Adobe Photoshop CS5 for expected size and DPI and saved in JPG format. Finally, the photomicrographs were numbered and placed in the manuscript. In the non-breeding season, in the interstitium, clusters of Leydig cells were found in abundant numbers. They looked foamy, white and easily visible. Their nuclei were found small and are located eccentrically. During recrudescence, the Leydig cell became less foamy and less white. In peak breeding season, the Leydig cells showed bigger in size and the nuclei became prominent. Cytoplasmic lipoidal material was lowest and cytoplasm was found dense pink. At the end of the breeding period, a heavy accumulation of lipid materials occurred in the Leydig cell. The clusters of Leydig cells were visible and looked white and foamy again. During this transition, disintegration of Leydig cells occurred after pycnotic nuclei of Leydig cells were found. During involution, a new generation of fibroblast-like cells appeared in the interstitium. Within the fibroblast-like cells, some of them became lipoidal by accumulating lipid materials. Thus a new generation of Leydig cells appeared in the interstitium. These lipoidal cells are thought to be a new generation of Leydig cells for the next breeding season. This study suggests that in seasonally breeding birds, new generation of Leydig cell is derived from fibroblastlike cells of the interstitium. The study concluded that the beginning of the regeneration phase marks the end of the secretory cycle of the Leydig cells although their ultimate fate seems to be in doubt. During this period a new generation of interstitial cells is derived from fibroblast-like cells. Further studies are needed on how quantitative information on histo-architectures of Leydig cells at the ultrastructural level correlates with serum LH (luteinizing hormone) and testosterone levels during breeding and nonbreeding season in wild birds.